2011
DOI: 10.1007/s10096-011-1473-x
|View full text |Cite
|
Sign up to set email alerts
|

Panbacterial real-time PCR to evaluate bacterial burden in chronic wounds treated with Cutimed™ Sorbact™

Abstract: The impact of polymicrobial bacterial infection on chronic wounds has been studied extensively, but standard bacteriological analysis is not always sensitive enough. Molecular approaches represent a promising alternative to the standard bacteriological analysis. This work aimed to assess the usefulness of a panbacterial quantitative real-time PCR reaction to quantitate the total bacterial load in chronic wounds treated with Cutimed™ Sorbact™, a novel therapeutic approach based on hydrophobic binding of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Cycle threshold (CT) was calculated using the SDS software on the ABI 7500 system. A qPCR assay for levels of the common Bacteroides genus was used as an internal control in the stool samples [32]. Samples that showed no amplification within 60 cycles were censored and assumed no template present or below detection limit.…”
Section: Quantitative Real Time Pcr (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cycle threshold (CT) was calculated using the SDS software on the ABI 7500 system. A qPCR assay for levels of the common Bacteroides genus was used as an internal control in the stool samples [32]. Samples that showed no amplification within 60 cycles were censored and assumed no template present or below detection limit.…”
Section: Quantitative Real Time Pcr (Qpcr)mentioning
confidence: 99%
“…Previously published primer and probes were used [20,32] were assessed by binary logistic regression to assess influence of Fn levels on disease group. Further, associations between Fn levels and disease progression were analysed by Spearman correlation analysis.…”
Section: Levels Ofmentioning
confidence: 99%
“…Another study by Gentili, Glanesini, and Balboni (2012) reported that 75% of the wounds showed a decrease in the bacterial count in the group treated with DACC-coated cotton acetate dressing. Cutting and McGuire (2015) Based on these results, it is found that DACC-coated cotton acetate dressing can be used as an alternative for infected wounds without the risk of bacterial resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Clinical observations indicated that Cutimed® Sorbact® resulted in completely successful therapy of 7 out of 20 patients and an improvement for 9 further patients, but an analysis of information on bacterial load obtained from wound swabs taken from the same patients did not correlate with clinical outcome. 11 This raises the importance of considering the differential effects of topical interventions on bacterial species unequally distributed throughout the wound environment. 12 Biofilm is not universally located at the surface of the wound 13 and it may be embedded within deeper tissue where it may not be affected by a therapy confined to the wound bed.…”
Section: Discussionmentioning
confidence: 99%